O Modelo negro: trajetórias do momento pós-colonial na história da arte - Tarabole, Ianá Marcelle da Silva (Universidade Federal de São Carlos, 2023)
The following work aims to explore the exhibition Le Modèle Noir as an artistic and cultural intervention that challenges stereotypes and negative representations, reflecting on the political struggles related to black representation. The general objective of the work is to carry out sociological reflections on the imaginary of black people in art history, exploring the exhibition catalog to understand the tensions, displacements and creations in the debate on pictorial representation, relating it to the bibliography on the representation of black people. in French postcolonial criticism. Furthermore, the study aims to show the context and gaps that the exhibition fills in the history of art, with an emphasis on the analysis of the Olympia painting, as a case study, and addressing the representation of black people that reverberates from the 18th century to modernity. . Through Post-Colonial and Cultural Studies, as a critical and theoretical framework, the exhibition is valued as a space for inclusive reflection on the history of France and its current issues, contributing to the dialogue between the past and the present and the appreciation of trajectories and representations of black populations. By deconstructing stereotypes, the exhibition promotes reflections on identity, representation and inclusion in contemporary society, also becoming a strategy for combating racial discrimination.
The black model: trajectories of the post-colonial moment in art history
Keywords: Le modèle noir; Representação negra; Estudos pós-coloniais; História da arte; Black representation; Postcolonial studies; Art history; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS